"Effects of using oxide fluxes as activating flux on Activated flux Tungsten Inert Gas welding" – A review. (2021) - Kumaar, S. Senthil; Korra, Nanda Naik
Abstract: Tungsten Inert Gas welding (TIG) is preferred in the Aerospace Industry where thin sections have to be welded with quality and precision. But, when thick sections are to be welded, conventional TIG welding is not usually preferred due to low penetration depth necessitating more passes. Activated flux Tungsten Inert Gas (A-TIG) welding was invented to improve productivity when welding thick sections. This study reviews the effects of using oxide fluxes in the A-TIG welding.